Distribution and Biology of the Invasive Weed Parthenium hysterophorus L. in Israel - Matzrafi, Maor; Raz, Hagai; Rubin, Baruch; Yaacoby, Tuvia; Eizenberg, Hanan (Frontiers in Agronomy, 2021)
Parthenium weed (Parthenium hysterophorus L.) (Asteraceae; Heliantheae) is an invasive allergenic species, that has invaded many countries worldwide, probably through imported pasture, grain seeds, and livestock feed. In recent years, there has been increasing concern about the spread of the invasive P. hysterophorus in agricultural and non-agricultural habitats across Israel. In addition, as P. hysterophorus is a quarantine plant, any contaminated produce exported will be rejected by the European market. The aims of the current study were to document the current distribution and invasiveness status of P. hysterophorus in Israel. Moreover, we aimed to study the life cycle and biology of P. hysterophorus. In this research, we detected invasion reports to new areas and habitats in the Jezreel valley, the Jordan valley and the Mediterranean coastal plain. Studying the biology of the weed, we found that optimal temperatures for seed germination are between 15 to 25oC. We observed that P. hysterophorus seeds are able to emerge from a depth of 0-3 cm only. P. hysterophorus thrives under high light intensities, our results show that under induced shading of 60 and 90%, significant reduction in biomass, height and number of flowers per plant were observed. Studying the biology and phenology of P. hysterophorus is a crucial step in the path to develop an integrated management program aimed to reduce further spread and negative impacts by P. hysterophorus.